Influence of catalysts on co-combustion of sewage sludge and water hyacinth blends as determined by TG-MS analysis. (January 2018) - Huang, Limao; Xie, Candie; Liu, Jingyong; Zhang, Xiaochun; Chang, KenLin; Kuo, Jiahong; Sun, Jian; Xie, Wuming; Zheng, Li; Sun, Shuiyu; Buyukada, Musa; Evrendilek, Fatih
Highlights: Co-combustion of biomass with K2 CO3, Na2 CO3 and MgCO3 was studied by TG-MS. Kinetic and thermodynamic parameters (Δ H, Δ S, Δ G ) were obtained through TGA curves. Main dominating steps were the organic volatile matter release and combustion stage. Na2 CO3 was the most effective among the tested catalysts for the co-combustion. Adding K2 CO3 catalyst to the biomass reduced the formation of flue gases. Abstract: Effects of the three metal carbonates (K2 CO3, Na2 CO3, and MgCO3 ) were quantified on catalytic co-combustion of the sewage sludge and water hyacinth (SW) blend using a thermogravimetric-mass spectrometric (TG-MS) analysis and kinetics modeling. The main dominating steps of the catalysts were the organic volatile matter release and combustion stage. Weighted mean values of activation energy ( E m ) were estimated at 181.18 KJ·mol −1, 199.76 KJ·mol −1, 138.76 KJ·mol −1, and 177.88 KJ·mol −1 for SW, SW + 5% K2 CO3, SW + 5% Na2 CO3, and SW + 5% MgCO3, respectively. The lowest E m occurred with SW + 5% Na2 CO3 . Overall, catalyst effect on co-combustion appeared to be negligible as indicated by Gibbs free energy ( Δ G ) . The normalized intensities of SW + MgCO3 were strongest . The addition of Na2 CO3 and MgCO3 to SW increased flue gases emissions (CO2, NO2, SO2, HCN, and NH3 ) of SW, whereas the addition of K2 CO3 to SW reduced flue gases emissions from the entire combustion process.